2023
DOI: 10.1172/jci.insight.156057
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of E-cadherin adhesions by COX-2/GSK3β signaling is a targetable pathway in metastatic breast cancer

Abstract: However, AJE has unlicensed patents related to the use of K14 as a biomarker in breast cancer and to the use of antibodies as cancer treatments. AJE's spouse is an employee of Immunocore.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Here, enzyme-linked immunosorbent assays (ELISAs) revealed that CXB-NPs could significantly reduce the PGE2 production in a concentration-dependent manner in all of the tested cell types, to the levels comparable to those of the parental CXB (Figure 2a-c). Furthermore, aware that the hormone-like effects of PGE2 can promote cancer cell proliferation and invasion, [27][28][29][30] we also investigated whether the PGE2-reduction by CXB-NPs can lead to inhibited proliferation of YUMM1.7 and CT26 cancer cells. As expected, and in line with our ELISA-based analyses of PGE2 levels, CXB-NPs effectively inhibited the proliferation of both cancer types to the levels similar to those of free CXB treatment (Figure 2d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Here, enzyme-linked immunosorbent assays (ELISAs) revealed that CXB-NPs could significantly reduce the PGE2 production in a concentration-dependent manner in all of the tested cell types, to the levels comparable to those of the parental CXB (Figure 2a-c). Furthermore, aware that the hormone-like effects of PGE2 can promote cancer cell proliferation and invasion, [27][28][29][30] we also investigated whether the PGE2-reduction by CXB-NPs can lead to inhibited proliferation of YUMM1.7 and CT26 cancer cells. As expected, and in line with our ELISA-based analyses of PGE2 levels, CXB-NPs effectively inhibited the proliferation of both cancer types to the levels similar to those of free CXB treatment (Figure 2d,e).…”
Section: Resultsmentioning
confidence: 99%
“…GSK3β, another type of serine/threonine protein kinase, was first described as a component of glycogen synthase regulation via its phosphorylation. As a core downstream component of PI3K/Akt [ 47 ], GSK3β mediates many biological processes in tumor cells and promotes the development and metastasis of many types of tumors through EMT [ 48 , 49 ]. One study has demonstrated that GSK3β is involved in the β-catenin/Snail1 pathway to promote the EMT process in bladder cancer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For staining of intracellular FOXP3 and IFN-γ, fixation buffer (420801) and intracellular staining permeabilization wash buffer (10×; 421002; BioLegend) were used. The specific experimental procedures were the same as those used in a previous study ( 12 ). Data were acquired on a flow cytometer (CytoFLEX, Beckman Coulter, Brea, CA, USA) and analyzed using the FlowJo software (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The overexpression of IDO1 can contribute to this detrimental effect by metabolizing the essential amino acid tryptophan into tyrosine, which is an effective T-cell metabolic inhibitor that inhibits T-cell proliferation ( 11 ). One study demonstrated that the COX-2 inhibitor celecoxib could enhance the efficacy of a breast cancer vaccine ( 12 ). Recent findings have spurred us to investigate the treatment of lung cancer using a combination of gemcitabine (GEM) and celecoxib.…”
Section: Introductionmentioning
confidence: 99%